Identification of Key Residues for Enzymatic Carboxylate Reduction - Stolterfoht, Holly; Steinkellner, Georg; Schwendenwein, Daniel; Pavkov-Keller, Tea; Gruber, Karl; Winkler, Margit (Frontiers in Microbiology, 2018)
Carboxylate reductases (CARs, E.C. 1.2.1.30) generate aldehydes from their corresponding carboxylic acid with high selectivity. Little is known about the structure of CARs and their catalytically important amino acid residues. The identification of key residues for carboxylate reduction provides a starting point to gain deeper understanding of enzymatic carboxylate reduction. A multiple sequence alignment of CARs with confirmed activity from the literature and recently identified in our lab revealed a fingerprint of conserved amino acids. We studied the function of conserved residues by multiple sequence alignments and mutational replacements of these residues. In this study, single-site alanine variants of Neurospora crassa CAR were investigated to determine the contribution of conserved residues to the function, expressability or stability of the enzyme. The effect of amino acid replacements was investigated by analysing enzymatic activity of the variants in vivo and in vitro. Supported by molecular modelling, we interpreted that five of these residues are essential for catalytic activity, or substrate and co-substrate binding. We identified amino acid residues having significant impact on CAR activity. His 237, Glu 433, Ser 595, Tyr 844, and Lys 848 abolish CAR activity, indicating their key role in acid reduction. These results may assist in the functional annotation of CAR coding genes in genomic databases. While some other conserved residues decreased activity or had no significant impact, four residues increased the specific activity of NcCAR variants when replaced by alanine. Finally, we showed that NcCAR wild-type and mutants efficiently reduce aliphatic acids.